Research, innovation and entrepreneurship in Saudi Arabia vision 2030 - Khan, Muhammad Khurram; Khan, Muhammad Babar (Abingdon, Oxon ; New York, NY : Routledge, 2020)
This book provides valuable insights into the Kingdom of Saudi Arabia (KSA) through a comprehensive examination of Vision 2030, an ambitious economic plan by the KSA to reinvent and diversify its economy from a heavy dependence on hydrocarbon to knowledge-based resources. Research, Innovation and Entrepreneurship in Saudi Arabia: Vision 2030 discusses how this initiative will assist the government in achieving its envisioned goals by creating a culture of research, innovation and entrepreneurship. It studies the current state ofthe fieldas well as new policies and reforms in Saudi Arabia which encompass education systems, ICT infrastructure and a vibrant innovation landscape that includes academia, the public and private sectors and civil society. The authors present a number of real-life case studies as a model of inspiration for cross-sector development. The book provides a source of inspiration for other nations in studying the KSA's determined and ambitious plans as a country in a transitioning journey, from a natural resources-based economy towards a knowledge-based country with considerable diversification in all sectors. This book is a useful reference for students, researchers and policy and decision-makers in understanding Saudi innovation and the economic diversification ecosystem.
OCLC-licensed vendor bibliographic record.
Keywords: Economic development -- Saudi Arabia; Entrepreneurship -- Saudi Arabia; Knowledge economy -- Saudi Arabia; Research and development projects -- Saudi Arabia; Saudi Arabia -- Economic conditions -- 21st century; Saudi Arabia -- Economic policy; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Development / Economic Development